Enhancing fast-food experiences: customer roles in using self-service technology - Samengon, Harnidah; Che Ishak, Farah Adibah; Ab Karim, Muhammad Shahrim; Ghazali, Hazrina; Arshad, Mohd Mursyid (Human Resource Management Academic Research Society, 2024)
Self-service technologies (SST) have transformed the fast-food industry by enhancing operational efficiency and customer experiences. However, the varying degrees of customer readiness and ability to engage with SST pose challenges, leading to potential frustration and impact on overall satisfaction. This study, guided by Service-Dominant (SD) Logic, explores customers' diverse roles when using SST in fast-food restaurants. Using a qualitative methodology, including semi-structured interviews and observations in Klang Valley fast-food restaurants, this research identified four primary customer roles: motivated co-creator of value, technological sweeper, responsible judge for value co-creation, and enforced worker. These roles highlight varying degrees of customer engagement and proficiency with SST. The findings emphasize the importance of recognizing these roles to optimize SST design and support systems, enhancing customer satisfaction and engagement. The study contributes to the SD Logic framework by illustrating the active role of customers in value co-creation, underscoring the need for adaptive and responsive service systems. These insights provide valuable guidance for fast-food restaurants aiming to improve SST experiences and service quality.